Volume Characteristics of Landslides Triggered by the MW 7.8 2016 Kaikōura Earthquake, New Zealand, Derived From Digital Surface Difference Modeling. Issue 7 (8th July 2020) - Massey, C. I.; Townsend, D.; Jones, K.; Lukovic, B.; Rhoades, D.; Morgenstern, R.; Rosser, B.; Ries, W.; Howarth, J.; Hamling, I.; Petley, D.; Clark, M.; et al.
Abstract: We use a mapped landslide inventory coupled with a 2‐m resolution vertical difference model covering an area of 6, 875 km 2 to accurately constrain landslide volume‐area relationships. We use the difference model to calculate the source volumes for landslides triggered by the MW 7.8 Kaikōura, New Zealand, earthquake of 14 November 2016. Of the 29, 519 mapped landslides in the inventory, 28, 394 are within the analysis area, and of these, we have calculated the volume of 17, 256 source areas that are ≥90% free of debris. Of the 28, 394 landslides, about 80% are classified as soil or rock avalanches and the remainder as mainly translational slides. Our results show that both the soil avalanches and the rock avalanches, ignoring their source geology, have area to volume power‐law scaling exponents (γ) of 0.921 to 1.060 and 1.040 to 1.138, respectively. These are lower than the γ values of 1.1–1.3 (for soil) and 1.3–1.6 (for rock) reported in the literature for undifferentiated landslide types. They are, however, similar to those γ values estimated from other coseismic landslide inventories. In contrast, for 50 selected rotational, translational (planar slide surfaces), or compound slides, where much of the debris remains in the source area, we found γ values range between 1.46 and 1.47, indicating that their slide surfaces were considerably deeper than those landslides classified as avalanches. This study, like previous studies on coseismic landslides, shows that soil and rock avalanches (disrupted landslides) are the dominant landslide type triggered by earthquakes and that they tend to be shallow. Key Points: We use a 2‐m resolution vertical difference model to estimate source volumes for 17, 256 landslides with sources ≥90% free of debris triggered by the MW 7.8 2016 Kaikōura Earthquake The model was derived by subtracting a tectonically adjusted pre‐EQ surface model from a post‐EQ model, covering an area of 6, 875 km 2 Landslide trigger mechanism, type/failure mode, and source material are critical for accurate estimation of landslide volumes from source‐area geometries